(untitled) (Research, Society and Development, 2020)
The use of clays to remove toxic metals present in water bodies has been tested by countless researchers. However, there is a need to give this type of material a destination after its use as an adsorbent. An option for an efficient destination of this material would be the incorporation of them in the constitution of the clay mixtures constituting ceramics. The objective was to verify the ability to remove Cu (II) and Ni (II) metal ions from ceramic matrices. The ability to retain metal ions in the structures of ceramics and their mechanical properties after the incorporation of galvanic sludge and effluent contaminated with toxic metals were evaluated. Leaching studies were carried out on the ceramic pieces to assess the possible release of metal ions to the environment. The results presented for the mechanical aspects of the ceramic pieces showed that the incorporation of the galvanic sludge, as well as the liquid effluent, did not compromise the mechanical properties of resistance of the produced pieces. Regarding the aspects related to leaching, the results showed that under certain conditions nickel or copper will not be released. The experimental results showed that leaching in basic and acidic media, there was no release of metals in samples moistened with effluent, but there was a release of nickel in the concentration of 10% of the sample with galvanic sludge and the release of copper in concentrations 6%, 8%, 10% of the samples with galvanic sludge. In all tests, there was no release of the two ions in neutral medium.